Criteres Du Traitement Non Operatoire Des Contusions Abdominales En Milieu Sous Equipe - Tchangai, Boyodi Katanga; Gayito, Adaba; Alassani, Fousseni; Dosseh, Ekoue David; Attipou, Komlan (European Scientific Journal, ESJ, 2017)
The criteria of non-operative operative management (NOM) of blunt abdominal trauma remains poorly defined in the context of low-income countries. Purpose: To validate a protocol for blunt abdominal trauma by specifying indications for NOM in a resource-limited setting. Material and Method: The study was prospective, carried out over a period of 12 months at Sylvanus Olympio Teaching Hospital Lomé (Togo). It included all patients over 15 years admitted for abdominal blunt trauma. Patients were subjected to NOM or surgery according to systolic blood pressure, response to resuscitation measures, clinical examination, peritoneal tap, abdominal plain radiograph and ultrasound. Results: Sixty-four patients, including 53 men and 11 women, were admitted in the study. The mean age was 27.8 years. Road traffic accidents were the circumstance of the occurrence in all cases. Pneumopéritoneum was found in 3 patients (5.45%). Abdominal ultrasound identified a solid organ injury in 24 patients (43.6%). Spleen lesions were the most frequent injuries. An extra-abdominal lesion was present in 23 patients (35.9%). NOM was initiated in 52 patients (81.25%) and effective in 46 patients (88.4%). The failure of the NOM was due to small intestine perforation in 2 patients, a bladder injury in 1 patient, active bleeding in 1 patient and hemodynamic instability resulting in nontherapeutic laparotomy in 2 patients. Death was observed in 8 patients (12.5%), 2 of whom were in the NOM group. Conclusion: criteria for the NOM of blunt abdominal trauma can be defined according to the local possibilities. Early diagnosis of digestive perforation should remain a priority during clinical monitoring.